Der Umgang mit Verkehr im suburbanen Raum: Raumstrukturelle Leitbilder und Gestaltungsspielräume - Stein, Axel; Wolf, Ulrike (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
Despite the high relevance of integrated land-use and transportation planning, its success in reducing traffic growth remains limited. Building on practical experiences in planning of transport and settlement structures in five regional case studies, this article provides a starting point for a renewal of overall models of spatial development. In doing so, the needs to meet the growing heterogeneity of suburbia and a more Strategic and practical orientation of these models are taken into account.